Internal and external oblique muscle asymmetry in sprint hurdlers and sprinters: A cross-sectional study - Adams, L.; Pace, N.; Heo, A.; Hunter, I.; Johnson, A. W.; Mitchell, U. H. (Journal of Sports Science & Medicine, 2022)
The abdominal muscles are vital in providing core stability for functional movements during most activities. There is a correlation between side asymmetry of these muscles and dysfunction. Thus, the purpose of this study was to evaluate and compare trunk muscle morphology and trunk rotational strength between sprint hurdlers, an asymmetrical sport, and sprinters, a symmetrical sport. Twenty-one trained collegiate sprint hurdlers and sprinters were recruited for the study (Hurdlers: 4M, 7F; Sprinters: 8M, 2F), average age (years) hurdlers: 20 ± 1.2; sprinters: 20.4 ± 1.9, height (cm) hurdlers: 172.6 ± 10.2; sprinters: 181.7 ± 4.5, and weight (kg) hurdlers: 67.6 ± 12.0; sprinters: 73.9 ± 5.6. Using real-time ultrasound, panoramic images of the internal oblique (IO) and external oblique (EO) were obtained at rest and contracted (flexion and rotation) in a seated position for both right and left sides of the trunk. While wearing a specially crafted shoulder harness, participants performed three maximal voluntary trunk rotational contractions (MVC). The three attempts were then averaged to obtain an overall MVC score for trunk rotation strength. Average MVC trunk rotational strength to the right was greater among all participants, p < 0.001. The IO showed greater and significant thickness changes from resting to contracted state than the EO, this was observed in all participants. The IO side asymmetry was significantly different between groups p < 0.01. Hurdlers, involved in a unilaterally demanding sport, exhibited the expected asymmetry in muscle morphology and in trunk rotational strength. Interestingly, sprinters, although involved in a seemingly symmetrical sport, also exhibited asymmetrical trunk morphology and trunk rotational strength.